Cerebrospinal Fluid Pulsation Stress Promotes the Angiogenesis of Tissue-Engineered Laminae. (2nd July 2020) - Li, Linli; He, Yiqun; Tang, Han; Mao, Wei; Ni, Haofei; Lyu, Feizhou; Dong, Youhai
Abstract : Background . Angiogenesis is a prerequisite step to achieve the success of bone regeneration by tissue engineering technology. Previous studies have shown the role of cerebrospinal fluid pulsation (CSFP) stress in the reconstruction of tissue-engineered laminae. In this study, we investigated the role of CSFP stress in the angiogenesis of tissue-engineered laminae. Methods . For the in vitro study, a CSFP bioreactor was used to investigate the impact of CSFP stress on the osteogenic mesenchymal stem cells (MSCs). For the in vivo study, forty-eight New Zealand rabbits were randomly divided into the CSFP group and the Non-CSFP group. Tissue-engineered laminae (TEL) was made by hydroxyapatite-collagen I scaffold and osteogenic MSCs and then implanted into the lamina defect in the two groups. The angiogenic and osteogenic abilities of newborn laminae were examined with histological staining, qRT-PCR, and radiological analysis. Results . The in vitro study showed that CSFP stress could promote the vascular endothelial growth factor A (VEGF-A) expression levels of osteogenic MSCs. In the animal study, the expression levels of angiogenic markers in the CSFP group were higher than those in the Non-CSFP group; moreover, in the CSFP group, their expression levels on the dura mater surface, which are closer to the CSFP stress stimulation, were also higher than those on the paraspinal muscle surface. The expression levels of osteogenic markers in the CSFP group were also higher than those in the Non-CSFP group. Conclusion . CSFP stress could promote the angiogenic ability of osteogenic MSCs and thus promote the angiogenesis of tissue-engineered laminae. The pretreatment of osteogenic MSC with a CSFP bioreactor may have important implications for vertebral lamina reconstruction with a tissue engineering technique.